Randomized comparative study of suspension femoral fixation device in graft position maintenance in anterior cruciate ligament reconstruction: EndoButton CL vs TightRope RT - Yoshimasa Ono; Yusuke Sato; Hiroki Mukai; Takahiro Enomoto; Seiji Kimura; Ryosuke Nakagawa; Ryuichiro Akagi; Yosuke Inaba; Yohei Kawasaki; Seiji Ohtori; Takahisa Sasho (Elsevier, 2021)
Background: In double-bundle anterior cruciate ligament reconstruction (ACLR), fixed-loop and adjustable-loop cortical suspensory devices are commonly used to fix the soft graft on the femoral side. However, few studies have compared in vivo elongation of the two devices. The purpose of this study was to determine whether EndoButton CL (EB) and TightRope RT (TR), the suspensory fixation devices used in ACLR, maintained their length in vivo from the time of surgery through the postoperative period in a randomized controlled trial. Methods: This study prospectively incorporated 30 patients undergoing initial ACLR at a single center. Participants were divided into two groups using a stratified randomization method with age and sex as assignment adjustment factors. EB or TR was used for fixation of the soft graft on the femoral side. The primary endpoint was to compare the elongation distance of the suspensory device. MRIs were taken within seven days after ACLR and 3,6,12 months postoperatively and measured by a radiologist in a blinded fashion. Secondary endpoints included the side-to-side difference in anterior translation, one leg hop test (HOP index), Lachman test, lateral pivot shift test, and Lysholm score one year postoperatively. Results: Twenty-eight patients (EB, n = 13; TR, n = 15) were followed for one year. There was no significant difference between EB and TR groups in elongation from the immediate postoperative period to 3, 6, 12 months after surgery. However, the non-inferiority of TR to EB (non-inferiority margin: 1.5 mm) was not proved by the difference in measured elongation between the two groups (TR - EB, lower 95% CI. AM: 1.80 mm; PL: 1.86 mm) at 6 months. There was no significant difference in anterior translation, HOP index, Lachman test, lateral pivot shift test, or Lysholm score. Conclusion: EB and TR had similar graft retaining ability in vivo for 12 months, but the non-inferiority of TR against EB was not verified statistically.